A deployable articulated mechanism enabled in-flight morphing aerial gripper. (January 2022) - Zhao, Na; Luo, Yudong; Wang, Gang; Shen, Yantao
Abstract: To further increase the adaptability and versatility of aerial vehicles, this paper presents a novel deployable quad-rotor enabled aerial gripper without integrating extra manipulators. In specific, the quad-rotor can morph/deploy in flight by actuating a simple but effective articulated rigid-elements based morphing mechanism, and the function of the gripper can be simultaneously achieved by following the extension/contraction of the deployable articulated mechanism. The proposed mechanism not only endows the quad-rotor with mechanical advantages such as high stiffness but also forms a morph-driven aerial gripper, which helps materialize a novel, compact yet efficient, and dual functional aerial vehicle. In addition, in order to control the morphing quad-rotor system, a morph-independent dynamic model and the corresponding control strategy are developed and presented. Extensive simulations and experiments on the proposed in-flight morphing mechanism and grasping functions of the gripper are performed. The results verify the effectiveness of the deployment/morphing mechanism and simultaneously enabled grasping functions, including handling different objects with various sizes, shapes, and textures. The results also validate that our deployment/morphing mechanism has less effect on flight behavior, but does own advantages of multi-maneuverability and morphological adaptation. Highlights: Designed a deployable quad-rotor that is morphologically adaptive to environments. Facilitated a morph-enabled aerial gripper w/o combining extra manipulator. Deployable mechanism has less effects in flight behavior but multi-maneuverability. Experiments validated the aerial gripping functions of the integrative mechanism.